The operation of sexual selection in the red junglefowl - Collet, J; Julie Collet (2010)
Sexual selection acts on traits that increase the reproductive success of an individual in competition with other individuals of the same sex over reproductive opportunities, through intra-sexual competition and inter-sexual mate choice. Because males benefit more from remating than females, they are subject to more intense sexual selection. Modern genetic tools have shown that females often mate promiscuously, thus prolonging sexual selection after insemination through intra-sexual (sperm competition) and inter-sexual (cryptic female choice) episodes. Despite increasing interest in post-copulatory sexual selection, the implications of sperm competition, cryptic female choice and underpinning mechanisms remain little understood. This thesis adopts an integrated approach to quantify the relative importance of post-copulatory episodes in the operation of sexual selection, elucidate their proximate mechanisms in the red junglefowl Gallus gallus. By combining behavioural observations of replicate groups with paternity data, I show that female promiscuity decreased the total opportunity for sexual selection in a group, but accounts for an unexpectedly large proportion of the variance in male reproductive success. By comparing the operation of sexual selection on multiple male traits, I show that post-copulatory sexual selection reinforced pre-copulatory sexual selection for male social dominance and that female preferred to mate with compatible males. I used experiments to study the mechanisms of post-copulatory sexual selection by studying the effect of seminal fluid in sperm competition and cryptic female choice in relation to male status and relatedness. Following previous work indicating that seminal fluid products influence sperm quality in this species, I tested in vivo whether the seminal fluid of an ejaculate acts differentially towards sperm from the same ejaculate and rival sperm, and found no evidence for this idea. Finally, I show that cryptic female choice can drastically bias the outcome of sperm competition, and that female fowl might bias paternity toward unrelated males.